Antibiotic-mediated dysbiosis leads to activation of inflammatory pathways - Taitz, Jemma J.; Tan, Jian; Ni, Duan; Potier-Villette, Camille; Grau, Georges; Nanan, Ralph; Macia, Laurence (Frontiers in Immunology, 2025)
IntroductionThe gut microbiota plays a pivotal role in influencing host health, through the production of metabolites and other key signalling molecules. While the impact of specific metabolites or taxa on host cells is well-documented, the broader impact of a disrupted microbiota on immune homeostasis is less understood, which is particularly important in the context of the increasing overuse of antibiotics.MethodsFemale C57BL/6 mice were gavaged twice daily for four weeks with Vancomycin, Polymyxin B, or PBS (control). Caecal microbiota composition was assessed via 16S rRNA sequencing and caecal metabolites were quantified with NMR spectroscopy. Immune profiles of spleen and mesenteric lymph nodes (MLNs) were assessed by flow cytometry, and splenocytes assessed for ex vivo cytokine production. A generalised additive model approach was used to examine the relationship between global antibiotic consumption and IBD incidence.ResultsAntibiotics significantly altered gut microbiota composition, reducing alpha-diversity. Acetate and butyrate were significantly reduced in antibiotic groups, while propionate and succinate increased in Vancomycin and PmB-treated mice, respectively. The MLNs and spleen showed changes only to DC numbers. Splenocytes from antibiotic-treated mice stimulated ex vivo exhibited increased production of TNF. Epidemiological analysis revealed a positive correlation between global antibiotic consumption and IBD incidence.DiscussionOur findings demonstrate that antibiotic-mediated dysbiosis results in significantly altered short-chain fatty acid levels but immune homeostasis in spleen and MLNs at steady state is mostly preserved. Non-specific activation of splenocytes ex vivo, however, revealed mice with perturbed microbiota had significantly elevated production of TNF. Thus, this highlights antibiotic-mediated disruption of the gut microbiota may program the host towards dysregulated immune responses, predisposing to the development of TNF-associated autoimmune or chronic inflammatory disease.